1990
DOI: 10.1104/pp.92.2.531
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of the Prokaryote Synechococcus sp. RF-1

Abstract: The prokaryotic Synechococcus sp. RF-1 exhibited a nitrogen fixation circadian rhythm with characteristics remarkably similar to the circadian rhythm of eukaryotes. The rhythm had a freerunning period of about 24 hours when the length of the preentrained cycle did not differ too much from 24 hours, and it was insensitive to changes in temperature from 220C to 330C. Because the endogenous rhythm of nitrogen fixation was not affected by a phase-shift of its previous cycles, the circadian rhythm in Synechococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 13 publications
2
67
0
Order By: Relevance
“…For many years, it was reasoned that since rapidly dividing microorganisms double in less than a day, a timing or predictive mechanism that extended longer than its doubling period would be of no use (Johnson et al, 2008). Disproving this notion, Huang et al (1990) demonstrated that the phototrophic marine cyanobacterium Synechococcus elongatus displays a robust circadian rhythm. More recently, it was shown that photoheterotrophic Halobacterium synchronize their physiologies with a light-dark cycle (Whitehead et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, it was reasoned that since rapidly dividing microorganisms double in less than a day, a timing or predictive mechanism that extended longer than its doubling period would be of no use (Johnson et al, 2008). Disproving this notion, Huang et al (1990) demonstrated that the phototrophic marine cyanobacterium Synechococcus elongatus displays a robust circadian rhythm. More recently, it was shown that photoheterotrophic Halobacterium synchronize their physiologies with a light-dark cycle (Whitehead et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…RF-l described by Huang and Chow (5) was used in this study. Unless stated otherwise, the cells were cultivated and quantitatively determined according to the methods described previously (7). The N-hydroxyethylpiperazine propane sulfonic acid-buffered BG-1 and the nitrate-free BG-1 media used are referred to as "BG-I 1" and "BG-l lo," respectively.…”
Section: Materials and Methods Organism And Cultivationmentioning
confidence: 99%
“…RF-1 exhibits a N2-fixing rhythm when growing under a diurnal LD2 regimen (5). The rhythm is an endogenous circadian rhythm that is controlled at the transcriptional level (3,6,7). Circadian rhythms are common in eukaryotes.…”
mentioning
confidence: 99%
“…Diurnal rhythms in nitrogen fixation, photosynthesis, amino acid uptake, and cell division were not immediately interpreted as the consequence of an endogenous biological clock. At least two groups recognized that these rhythms were reminiscent of eukaryotic circadian cycles (Sweeney and Borgese 1989;Huang et al 1990), and T.-C. Huang's group performed experiments to demonstrate that rhythms of amino acid uptake in Synechococcus (now Cyanothece) RF-1 persist under constant conditions, reset the timing of peak activity in response to an environmental signal, and are temperature-compensated (Huang et al 1990). With these three criteria fulfilled, a cyanobacterial rhythm was demonstrated to share the hallmarks of eukaryotic circadian rhythms (Dunlap et al 2004).…”
Section: Introductionmentioning
confidence: 99%